Contacto interétnico en el norte de Tierra del Fuego : la Misión Salesiana La Candelaria (Río Grande) y la salud de la población Selk’nam (1895-1931) - Romina Casali (Nuevo mundo - Mundos Nuevos, 2012)
This thesis addresses the consequences of inter-ethnic contact of the Selk'nam (onas) population -who occupied most of the steppe of Tierra del Fuego towards the end of the nineteenth century- by the time the Argentinean and Chilean colonization of Tierra del Fuego began to emerge. To understand the synergistic behavior of the diverse factors that influenced the health of this community, we offer a detailed study of the missionary daily life in accordance to the social, economic, political and ecological lifestyle of the region. From a historiographic perspective, this thesis contributes to the specific discussion around the impact of contact on the island, a subject regularly addressed by anthropology and archaeology. We contribute -with a case study- to major discussions related to the impact of colonization on health and demographic structure of the aboriginal populations as well as on the role of specific diseases such as tuberculosis, in particular. This paper thoroughly describes the disturbances caused by the imposition of a social system completely unrelated to the hunter-gatherer lifestyle of the selk’nam : nutrition, rest, work, contagious situations, architecture, diseases, social tension, etc., without neglecting the biological substrate and natural history of the diseases involved, In doing so, we highlight the importance of the social and cultural disruptions on the rise of morbidity and mortality beyond (and in addition to) issues such as : the genetic structure, the immunological history of the populations involved or co-evolution between the host and pathogen.